2006
DOI: 10.1627/jpi.49.214
|View full text |Cite
|
Sign up to set email alerts
|

Simple Syngas Detector for High-throuput Screening Reactor Using Color Reaction at High Pressure

Abstract: 1.HTS: high-throughput screening The high-throughput screening reactor for high pressure oxidative reforming of methane requires a new simple syngas detector operating under high pressure, because the number of parallel reactors with the conventional detection system is limited by the complexity of the pressure reducing unit. Reduction of metal oxide with color change was applied to the detection system. Copper oxide was supported on the fi lter made of alumina, and the fi lter was placed underneath the catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2008
2008

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…[364] In situ detection of the formation of syngas through the optical read-out of Cu reduction has been applied by Omata et al for HTS of catalysts for oxidative methane reforming under pressure. [365] Uniformly sized, multimetallic catalyst nanoparticles deposited onto different substrates (for example, g-Al 2 O 3, CeO 2 , TiO 2 , SiO 2 , or Y-ZrO 2 ) can be prepared by highthroughput through pulsed laser ablation (HT-PLA). The method was developed by Senkan et al, and its use was demonstrated in a search for catalysts for the selective oxidation of propylene.…”
Section: Combinatorial Materials Researchmentioning
confidence: 99%
“…[364] In situ detection of the formation of syngas through the optical read-out of Cu reduction has been applied by Omata et al for HTS of catalysts for oxidative methane reforming under pressure. [365] Uniformly sized, multimetallic catalyst nanoparticles deposited onto different substrates (for example, g-Al 2 O 3, CeO 2 , TiO 2 , SiO 2 , or Y-ZrO 2 ) can be prepared by highthroughput through pulsed laser ablation (HT-PLA). The method was developed by Senkan et al, and its use was demonstrated in a search for catalysts for the selective oxidation of propylene.…”
Section: Combinatorial Materials Researchmentioning
confidence: 99%
“…Assembly of the detector disk was considered, 27 and the outlines are illustrated in Figure 6. Figure 6a is the principal design.…”
Section: Resultsmentioning
confidence: 99%
“…[364] In-situ-Detektion der Synthesegasbildung durch optische Erkennung einer Cu-Reduktion wurde von Omata et al beim HT-Screening von Katalysatoren für die oxidative Methanreformierung unter Druck eingesetzt. [365] Multimetallkatalysatornanopartikel enger Größenvertei-lung können im Hochdurchsatz durch gepulste Laserablation (HT-PLA) auf unterschiedlichsten Substraten (z. B.…”
Section: Ht-untersuchungen Für Die Enwicklung Von Polymerenunclassified